1989
DOI: 10.1093/ajh/2.4.259
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria and Casual and Ambulatory Blood Pressure Monitoring in Normotensives and in Patients With Borderline and Mild Essential Hypertension

Abstract: Several reports suggest that urinary albumin excretion may be elevated in patients with essential hypertension and that this index may be a good predictor for cardiovascular complications. The aim of this study was to compare 24-hour urinary albumin excretion in a group of normotensives, borderline, and untreated mild hypertertensives and to assess, in a subgroup of them, the possible relations between microalbuminuria and arterial blood pressure. Fifteen normotensives, 16 borderline, and 19 mild hypertensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
2
3

Year Published

1991
1991
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(60 citation statements)
references
References 0 publications
4
51
2
3
Order By: Relevance
“…Although this has previously been demonstrated in 1966 by Sokolow et al 9 and has been confirmed by other studies assessing targetorgan disease in the heart, kidneys, brain and blood vessels, [11][12][13][14][15] according to the data presented here, the relationship between criteria of left ventricular mass and blood pressure in a selection of treated hypertensive patients is weak (at most 0.28). This is in contrast with the relationship found in studies including subjects with a wide spectrum of blood pressure values, including normotensive and untreated hypertensive subjects (correlation coefficients up to 0.56).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although this has previously been demonstrated in 1966 by Sokolow et al 9 and has been confirmed by other studies assessing targetorgan disease in the heart, kidneys, brain and blood vessels, [11][12][13][14][15] according to the data presented here, the relationship between criteria of left ventricular mass and blood pressure in a selection of treated hypertensive patients is weak (at most 0.28). This is in contrast with the relationship found in studies including subjects with a wide spectrum of blood pressure values, including normotensive and untreated hypertensive subjects (correlation coefficients up to 0.56).…”
Section: Discussionsupporting
confidence: 80%
“…[9][10][11][12][13][14][15] In addition, single office blood pressure only weakly predicts coronary events. [9][10][11][12][13][14][15] However some of these studies have been criticised in terms of trial design. 16,17 Furthermore with regards to the development of target organ damage, controversy exists regarding the relative importance…”
Section: Introductionmentioning
confidence: 99%
“…30 Somewhat unexpectedly, the association between albumin excretion and nighttime blood pressure (the period of urine production in our study) was in no way stronger than for the daytime blood pressure. Others studies have reported a similar tendency for stronger correlations in hypertensive than normotensive individuals 27 and in ambulatory pressures compared with casual, 31 whereas diastolic pressures have been reported superior to systolic pressures, 31 in contrast with our findings. Some studies have found no statistically significant correlations between blood pressure and albuminuria.…”
Section: Discussionsupporting
confidence: 63%
“…57 Second, clinic blood pressure reflects to only a limited degree 24-hour average blood pressure, 58 -59 in both untreated and treated hypertension. 6 And third, compared with clinic blood pressure, 24-hour or daytime mean blood pressure correlates more closely with the overall end-organ damage of hypertension 59 ' 60 and with markers of individual organ damage such as left ventricular hypertrophy, 6162 left ventricular systolic and diastolic function, 63 ' 64 albuminuria, 65 and cerebral ischemia. 66 Overall or individual organ damage also bears a direct relation with blood pressures occurring at work, 62 with the number of daytime blood pressure peaks, 63 with nighttime blood pressure values, 4767 and with 24-hour blood pressure variability.…”
Section: Figure 12 Scatterplots Show Regression Coefficients Of the mentioning
confidence: 99%